PENGEMBANGAN LKS BERBASIS VIDEO PERCOBAAN HUKUM KEKEKALAN MOMENTUM SUDUT UNTUK PEMBELAJARAN FISIKA SMA - Rahayu, Yendi Kusuma Rahayu Kusuma; Sudrajad, Hendar Sudrajad; ', Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This R & D research aimed Â to design, create, and validating an experimental video-based worksheets of the law of conservation of angular momentum as a media of physics learning in senior high school. This research was conducted at the Laboratory of Physics Education Riau University in December 2014 until June 2015. The research products developed based on the flowchart and storyboard that has been designed. Three lecturers physical education and two senior teachers of physics has validated this product. The finding of the research showed that the video of angular momentum conservation laws experiments has a validity index of 3.48 and Â video-trial based worksheets the law of conservation of momentum has a validity index of 3.49. Based on the validity index, showed that experimental video and video-trial based worksheet declared in valid. Keywords: the law of the conservation of angular momentum, video-trial based worksheet